2018
DOI: 10.3390/cancers10080261
|View full text |Cite
|
Sign up to set email alerts
|

The Endometriotic Tumor Microenvironment in Ovarian Cancer

Abstract: Women with endometriosis are at increased risk of developing ovarian cancer, specifically ovarian endometrioid, low-grade serous, and clear-cell adenocarcinoma. An important clinical caveat to the association of endometriosis with ovarian cancer is the improved prognosis for women with endometriosis at time of ovarian cancer staging. Whether endometriosis-associated ovarian cancers develop from the molecular transformation of endometriosis or develop because of the endometriotic tumor microenvironment remain u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 205 publications
(268 reference statements)
0
36
0
Order By: Relevance
“…Ovarian cancer is initially associated with pelvic inflammatory disease, such as endometriosis, demonstrating a similarity between the processes of inflammation and carcinogenesis. Endometriotic cells adapt to survive in the unique microenvironment conditions with high levels of iron, inflammatory cytokines and chemokines (98). Microenvironment-cell interplay may modulate the major signaling pathways associated with cell cycle regulation, growth factor signaling, immune and inflammatory pathways, and the extracellular matrix remodeling, which results in phenotype transformation (99).…”
Section: Similar Epigenetic Modifications: Gene-environment Interactimentioning
confidence: 99%
“…Ovarian cancer is initially associated with pelvic inflammatory disease, such as endometriosis, demonstrating a similarity between the processes of inflammation and carcinogenesis. Endometriotic cells adapt to survive in the unique microenvironment conditions with high levels of iron, inflammatory cytokines and chemokines (98). Microenvironment-cell interplay may modulate the major signaling pathways associated with cell cycle regulation, growth factor signaling, immune and inflammatory pathways, and the extracellular matrix remodeling, which results in phenotype transformation (99).…”
Section: Similar Epigenetic Modifications: Gene-environment Interactimentioning
confidence: 99%
“…In this study, high expression of MACC1 mRNA in endometrioid cancer patients was significantly associated with unfavorable OS, although PFS did not show statistically significant results. Recently, the interest in carcinogenesis of endometrioid or clear cell carcinoma associated with endometriosis has been increasing [ 26 ]. However, this study was limited in the number of endometrioid cancer cases to produce definite conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…In general, both clear cell and endometrioid OCs commonly display highly frequent mutations in ARID1A, CTNNB1, KRAS, PIK3CA and PTEN, irrespective of associated endometriosis [156]. McConechy et al [157] however in a study of the mutation profiles of EEC and EAOC (morphologically similar tumors) have reported differences in PTEN and CTNNB1 profiles.…”
Section: Oncogenes and Tumor Suppressor Genesmentioning
confidence: 99%
“…It is likely that the inflammatory and oxidative-environmental niche during oncogenesis may be reflective of such distinct mutation patterns observed in EEC as compared to EAOCs. While it is plausible that persistent inflammatory niche at ET lesion may cause genetic and epigenetic changes specific to EAOCs [97,158], the question whether OCs with and without concurrent endometriosis develop through common pathogenic pathways remains unsettled due to the fact that a large number of women with EAOCs do not have endometriosis at the time of staging and 1 out of 3 patients with endometrioid or clear-cell OCs show concurrent endometriosis [156]. Also, studies often fail to report whether endometriosis is present with concurrent AE, absence of which may give erroneous construction of such an inference.…”
Section: Oncogenes and Tumor Suppressor Genesmentioning
confidence: 99%
See 1 more Smart Citation